Single amino acid substitution in constant region 1 or 4 of gp120 causes the phenotype of a human immunodeficiency virus type 1 variant with mutations in hypervariable regions 1 and 2 to revert. - Wang, W K (1996)
The second major cysteine loop of human immunodeficiency virus type 1 envelope glycoprotein gp120 contains 5 to 11 consensus N-linked glycosylation sites, which is disproportionately higher than the number of such sites found in other regions of gp120. Amino acid substitutions introduced at three of six N-linked glycosylation sites in this region of an infectious molecular clone, HXB2, resulted in severe impairment of virus infectivity. Isolation and genetic characterization of a revertant of this mutant revealed an isoleucine-for-valine substitution at position 84 in constant region 1 and an isoleucine-for-methionine substitution at position 434 in constant region 4. Further mutational analysis indicated that either isoleucine substitution was sufficient to confer the revertant phenotype. These findings demonstrate that V1/V2 not only functionally interacts with C4, as previously reported, but also interacts with C1. The observation that compensatory changes do not involve regeneration of N-linked glycosylation sites in the second major cysteine loop suggests that replication of human immunodeficiency virus type 1 in vitro is independent of the presence of a disproportionate number of N-linked glycosylation sites within this loop.